Inclusión financiera en las Cooperativas de Ahorro y Crédito Segmento 3 de la provincia de Chimborazo, 2023 - Peña Quishpe, Alisson Pamela (2025)
Financial inclusion in the Savings and Credit Cooperatives of Segment 3 in the province of Chimborazo is a crucial issue for the region's economic development. This study analyzed the degree of financial inclusion of these cooperatives through surveys of members and clients and interviews with experts from the cooperatives. The surveys revealed that many members and clients still face barriers to accessing financial products, such as a lack of information and knowledge. Interviews with experts indicated that credit unions should implement more effective financial education strategies and promote confidence in their services. The need was also identified to improve the technological infrastructure to facilitate access to digital services, especially in rural areas. In conclusion, fostering financial inclusion in Segment 3 Credit Unions in Chimborazo is essential to promote sustainable development and improve the quality of life of its members.